Fabrication and electrochemical response of pristine graphene ultramicroelectrodes. (15th June 2021) - Goodwin, Stefan; Coldrick, Zachary; Heeg, Sebastian; Grieve, Bruce; Vijayaraghavan, Aravind; Hill, Ernie W.
Abstract: Ultramicroelectrodes (UMEs) are electrochemical working electrodes with at least one dimension less than 25 μm. Here, we demonstrate a method to fabricate pristine (contamination and doping-free) monolayer graphene UMEs and characterise its electrochemical properties. Graphene is particularly sensitive to both contamination from device fabrication and doping from the substrate, and these effects are detrimental to accurate measurements of fundamental electrochemical properties as well as electrochemical electrode applications. We demonstrate a UME design and fabrication steps which ensure that the electro-active surface of the graphene never comes into contact with contaminants such as process polymers and solvents, has a well-defined area due to self-aligned fabrication, and we shield the converse side of the graphene monolayer with the highly inert dielectric hexagonal boron nitride (h-BN). Cyclic voltammetry demonstrates the expected steady-state behaviour for a UME in the hemispherical diffusion regime. The reduction of IrCl6 2− in weak KCl electrolytes was employed to investigate the electron transfer characteristics of the pristine graphene UMEs and the reproducibility of the measurements. Values of the standard rate constant, k 0 and the transfer coefficient, α were measured to be 3.04 ± 0.78 × 10 −3  cm s −1 and 0.272 ± 0.024 respectively. These values are consistent for monolayer graphene with reduced charge doping from contaminants and the substrate. This is further confirmed by Raman spectroscopy measurements of the graphene UME before and after the electrochemical measurements. Graphical abstract: Image 1